2013
DOI: 10.1177/0018726712472915
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Job Demands-Resources model in cross-national samples: Cross-sectional and longitudinal predictions of psychological strain and work engagement

Abstract: The Job Demands-Resources (JD-R) model proposes that employee health and performance are dependent upon direct and interacting perceptions of job demands and job resources. The JD-R model has been tested primarily with small, cross-sectional, European samples. The current research extends scholarly discussions by evaluating the full JD-R model for the prediction of psychological strain and work engagement, within a longitudinal research design with samples of Australian and Chinese employees ( N = 9404). Job r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 59 publications
6
86
2
Order By: Relevance
“…Finally, the mediation analyses showed that attitudes and PBC, mainly via self‐efficacy, mediated the effect of job resources (fully) and job demands (partially) on intentions (supporting Hypothesis 4). In line with the basic job demands and resources assumptions (Brough et al, ; Demerouti et al, ), the current study found that the motivational processes associated with high‐resource factors were linked to increased intentions with regard to fruit and vegetable consumption, low‐fat diet and physical activity, mediated by the changes in attitudes and PBC. On the other hand, higher job demands lead to higher fat consumption through attitudes and PBC, suggesting a negative effect of strain processes produced by (usually negative) job demands.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, the mediation analyses showed that attitudes and PBC, mainly via self‐efficacy, mediated the effect of job resources (fully) and job demands (partially) on intentions (supporting Hypothesis 4). In line with the basic job demands and resources assumptions (Brough et al, ; Demerouti et al, ), the current study found that the motivational processes associated with high‐resource factors were linked to increased intentions with regard to fruit and vegetable consumption, low‐fat diet and physical activity, mediated by the changes in attitudes and PBC. On the other hand, higher job demands lead to higher fat consumption through attitudes and PBC, suggesting a negative effect of strain processes produced by (usually negative) job demands.…”
Section: Discussionsupporting
confidence: 81%
“…Similar difficulties in finding interaction effects have been found in previous empirical research using the related Job Demands Control model (e.g., De Jonge & Dormann, 2003) and more recently in the JD-R model (Brough et al, 2013). A possible explanation might be the mismatch between job demands, job resources, and job outcomes with regard to the same domain of human psychological functioning (Brough et al, 2013). Hypothesis 1 was confirmed: TPD at work appeared to have a strong relationship with flexible competence, which underlines the importance of TPD at work.…”
Section: Reflectionssupporting
confidence: 79%
“…The validity of the JD-R model has been confirmed in the light of predicting employee health and wellbeing (e.g., Brough et al, 2013;Cotter & Fouad, 2013;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2007) and organizational outcomes, like turnover intention and organization commitment (e.g., Hu, Schaufeli, & Taris, 2011). However, in the context of learning, and especially in the context of TPD at work and flexible competence, the validation of the model is limited (Evers, Kreijns, van der Heijden, & Gerrichhauzen, 2011a).…”
Section: Introductionmentioning
confidence: 95%
“…Characteristics of an organization that is ready to adopt change include: the presence of multilevel participatory processes, a thorough understanding of the mechanics of the stress process, an awareness of the roles and requirements of all employees to enact change, and a shared responsibility for promoting employee well-being (Biggs 2011 ;. Recent discussions have, for example, considered the length of the time-lag required to demonstrate any changes in the targeted criterion variables Brough and O'Driscoll 2010 ;Brough et al 2013 ;de Jonge and Dormann 2006 ;de Lange et al 2003 ;van der Klink et al 2001 ;Zapf et al 1996 ). Another overlooked issue for many organizational interventions is the dissonance between messages communicated as a result of the intervention and actual managerial actions .…”
Section: Key Organizational Intervention Lessonsmentioning
confidence: 99%
“…11. The ability to choose a time-lag based on theoretical reasoning is limited, however, due to the lack of empirical and theoretical research focused on time-lags in intervention evaluation research Brough et al 2013 ). For example, in our corrections intervention (described in Chap.…”
Section: Key Organizational Intervention Lessonsmentioning
confidence: 99%